Can GLP-1 receptor agonists slow the progression of Autosomal Dominant Polycystic Kidney Disease? - Hamad Ali; Barrak Alahmad; Fahd Al-Mulla (BMC Nephrology)
Abstract GLP-1 receptor agonists revolutionized diabetes therapy and offer cardiorenal protection in diabetic kidney disease. Their potential in Autosomal Dominant Polycystic Kidney Disease (ADPKD) is now being explored. Preclinical findings and metabolic improvements (obesity, hypertension, inflammation) indicate promise. Further clinical studies are required to ensure efficacy and safety before clinical integration can be considered. Clinical trial number: Not applicable.